3(q-6)=15

Simple and best practice solution for 3(q-6)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(q-6)=15 equation:


3(q-6)=15

We simplify the equation to the form, which is simple to understand
3(q-6)=15

Reorder the terms in parentheses
+(+3q-18)=15

Remove unnecessary parentheses
+3q-18=+15

We move all terms containing q to the left and all other terms to the right.
+3q=+15+18

We simplify left and right side of the equation.
+3q=+33

We divide both sides of the equation by 3 to get q.
q=11

See similar equations:

| n/-9-7=-4 | | ln1/ln2 | | f(x)=10x^3+37x^2+37x+6 | | 88=21x+6y | | 3x^2-4x+5=3 | | .5x+5=.6(x-10) | | 0.5/3.8 | | a/4=27/18 | | -5(-x+2)=-x+4(x-5) | | 3.8/0.5 | | -9t=-7/2 | | 48x+18y=252 | | 5n+4=74 | | -7x-30=0 | | 12=8+r | | 180=148+18+3x+y | | 6x-8+8=2 | | 6x-6=-8 | | 38+7h=8(h+4) | | -30=2(x+5) | | 139+10x-11+121+9x-17+7x+6+153+9x-14+8x+15=1080 | | -7+n+3-7n=n-4 | | x-2(1.5)=-1 | | 4x^2=-6x-11 | | 6/5=x(-5/6) | | 2(x-5)+15=-23 | | 0.4(1-5x)=-0.5(4x+4) | | 6x+x=x+1+4x+15 | | 12x+60=y | | 6/5=x/(5/6) | | 6/5=x/5/6 | | 0.2*(3b-15c)+6c= |

Equations solver categories